Out of Love and Desire: DIY Agency and Amateur Effort in the Public Realm. - KOH, GERMAINE (Journal of Canadian Studies, 2025)
Using the framework of a journey of learning, the author relates her own development toward producing community-engaged projects focused on do-it-yourself activity and a position advocating for more trust in amateur efforts. She addresses related subjects that build toward this position, with reference throughout to some of her own and community projects. First, she argues for the value of non-specialization and crossing disciplinary boundaries and problem-making. That is related to translation, code-switching and skill sharing as tools that enable one to operate across disparate fields. She gives examples of community efforts expressing collective intent that change urban space by understanding it as a field of play. This leads to a summary of theories of invention through play, especially risky play as a form of play that has many collective benefits. The valuing of risk, experimentation, and testing the limits of rules is then associated with creative processes and certain initiatives the author is involved with that deliberately challenge regulations, sometimes with an intention to oppose colonial systems. This leads to a discussion of the real benefits of citizen and amateur effort in building the character of social space and then an argument to view doing-it-yourself as both a right and a need. The article ends with a call to authorities to find more ways to trust and entrust amateur efforts.